THE URGENCY OF COOPERATIVE LEARNING IN THE IMPLEMENTATION OF THE 2013 CURRICULUM ON ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT SMA NEGERI 1 WATAMPONE - Sarifa Suhra; Samsinar S; Sarifa Halijah; Sarifa Nursabaha (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This paper examines the urgency of cooperative learning in the implementation of the 2013 curriculum in Islamic education subjects at SMA Negeri 1 Watampone. This study uses a qualitative approach. data obtained through interviews and observations. The results showed that; cooperative learning is known as group learning. However, cooperative learning is more than just group learning or group work because cooperative learning allows open interaction and effective interdependence among group members. PAI teachers at SMA Negeri 1 Watampone apply 3 types of cooperative learning methods in implementing the 2013 curriculum, namely: contextual learning, role playing, and participatory learning. While the urgency of cooperative learning is quite a lot of them; Embedded character values in the group learning process so that a culture of cooperation and mutual respect is formed naturally. Learning while playing, learning becomes comfortable and students are more motivated to learn, independent learn, can accept differences, receive feedback, are able to turn information and abstract learning abilities into reality, and Interaction during cooperative learning can increase motivation and provide stimulation to think for students.